Professional values, ethics, and professionalism of public relations practitioners = Nilai-nilai profesional, etika dan profesionalisma dalam pengamal perhubungan awam - Syed Abdullah Idid, Syed Arabi; Arandas, Mohammed Fadel (School of Media and Communication Studies (MENTION), Faculty of Social Sciences and Humanities Universiti Kebangsaan Malaysia, 2016)
This study explores the influence of education, length of service, professionalism, and ethics on the professional values of public relations practitioners in Malaysia. A total of 427 questionnaires were distributed to public relations practitioners in Malaysia, and 322 questionnaires were returned. The study included 61% female respondents, and 39% male respondents. The study analyzed and identified the influence of professionalism and ethics on professional values of public relations practitioners. Additionally, the study examined whether education and experience influence professional values through professionalism, and code of ethics. Six hypotheses were tested to answer the research questions. The results from this study fully supported the hypotheses indicating that professionalism and ethics had an influence on professional values of public relations practitioners. The results also showed that education influenced both professionalism and ethics, and length of service influenced both professionalism and ethical practice.